An expert system for maintenance scheduling. (1st January 1999) - Chan, F.T.S.; Mak, K.L.; Law, F.S.M.
An expert system is developed for the efficient scheduling of the maintenance department in an aeronautic engine company. The Proposed Expert Scheduling System (PESS) consists of a database, a knowledge base, an inference mechanism, and an operating mechanism. The database of the PESS can be local and global, and consists of the facts supplied by the users via user interface. During the consultation process, some intermediate conclusions can also be stored into the global database for further decision-making. Evaluation of the PESS is also discussed.